Health care delivery, access and utilisation in emerging communities and urban slums of south west Nigeria - Lawal, Saheed Akinmayọwa (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2014)
In Nigeria, over 60 percent of the population lack access to modern health care facilities. Low access and effective utilisation even where available, are affected by inadequate health workforce, low quality of care, distance, and poor policy implementation. This research examines the nature of health care in emerging communities and urban slums of south west Nigeria. The study synthesises Giddens’ Structuration theory, Dahlgren and Whitehead’s Social model of health, and Andersen and Newman’s Framework of health service utilisation as its theoretical framework.
Keywords: Global health, Ph.D.; Ph.D. Trinity College Dublin